Treatment modalities for single missing teeth in a Turkish subpopulation: an implant, fixed partial denture, or no restoration - Zeynep Özkurt; Ender Kazazoğlu (Journal of Dental Sciences, 2010)
Background/purpose: The aim of this study was to compare the frequency of 3 treatment alternatives in a Turkish subpopulation with a single missing tooth: implant retained crowns (IRCs), fixed partial dentures (FPDs), and no replacement. Materials and methods: A study comparing 3 different treatment alternatives for a single missing tooth was conducted. Data were collected by panoramic radiographic examination. Age, gender, and treatment method for a single missing tooth were recorded. Differences between the groups were examined using one-way ANOVA, and multiple comparisons were evaluated by using Tukey’s HSD test. A Chi-squared test was used to compare qualitative data. The significance level was set to 5%. Results: Of 1953 examined radiographs, 218 (11.16%) patients were found to have a single missing tooth. Of these 218 patients, 101 (46.3%) had FPD restorations, and 23 (10.6%) had IRCs. Ninety-four (43.1%) patients had no restorations. The mean age of patients with FPDs was significantly higher than that of patients with no restorations (P<0.01). There were no significant differences between treatment modality or gender (P>0.05). FPDs and IRCs in the anterior region were significantly more prevalent compared to the posterior region (P<0.01). Conclusions: The great majority of patients with a single missing tooth had a higher interest in FPDs than IRCs. Patients with no replacement were also prevalent.